Next-generation sequencing yields the complete mitochondrial genome of Microhyla beilunensis (Anura: Microhylidae). Issue 3 (2nd July 2020) - Feng, Lei; Zheng, Wei-Cheng; Chen, Zhi-Qiang; Zhong, Jun-Jie; Ding, Guo-Hua
Abstract: The complete mitochondrial genome (mtDNA) of Microhyla beilunensis (Anura: Microhylidae) was sequenced and annotated. The length of mtDNA sequences of M. beilunensis was 16, 721 bp, and encoded 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and a control region. The overall nucleotide composition of this genome was 29.1% A, 24.5% C, 14.5% G, 31.9% T, with a total A + T content of 61%. Phylogenetic analysis using Bayesian Inference (BI) method revealed that M. beilunensis was closely related with other 8 species from the genus Microhyla . The mtDNA dataset could be utilized for studying the molecular ecology and population genetics of Microhylid frogs.